Caracterización de infecciones por bacterias productoras de BLEE en un hospital de referencia nacional. - Tejada Llacsa, Paul J. (2015)
Background: Resistance by extended-spectrum beta-lactamase (ESBL) is the most common antimicrobial resistance and of public health importance. Objectives: To describe ESBL producing bacteria characteristics in a national reference hospital. Design: Cross sectional, descriptive study. Setting: Hospital Nacional Daniel Alcides Carrión, Callao, Peru. Materials: Records of secretion cultures done in the hospital Laboratory of Microbiology during 2012. Methods: Patient data (age, sex and service from which the sample was received) and sample data (date of collection, sample type, microorganism found, sensitivity and detailed classification as ESBLproducing bacteria) were analyzed. Main outcome measures: Characteristics of infections by ESBL-producing bacterias. Results: Study included 3 149 samples, 70.9% (2 235) from female patients; 29.4% were cultures positive for ESBL-producing bacteria. Critical services had the highest prevalence, and months with highest occurrence were April (34.7%) and July (34.7%). Both, E. coli (72.4%) and Klebsiella sp. (20.0%) were the most prevalent. No imipinem resistance was found for E. coli or Klebsiella sp. Conclusions: The prevalence was similar to that of Latin America (34.6%). More evidence of high prevalence in outpatients and patients over 46 year-old is presented, considering it a public health problem.